Epidemiological and clinical characteristics of hospitalized unintentional injuries among children in central China from 2017–2023 - Wang, Meng; Cheng, Yibing; Wang, Haijun; Lin, Li; Shen, Yuelin (Frontiers in Pediatrics, 2024)
Objectives To examine the epidemiological and clinical characteristics of hospitalized unintentional injuries among children in Central China and theoretically propose preventive and control measures. Methods We conducted a retrospective study of children aged 0–18 years with unintentional injuries who were admitted to a tertiary hospital in Central China from January 2017 to December 2023. We examined various aspects of the unintentional injuries, including age, gender, urban-rural distribution, external causes, trends, location of injury, cost, and length of stay. Results A total of 20,166 children with hospitalized unintentional injuries were enrolled. The median age with IQR was 2.8 (1.6, 5.1) years, with majority of the patients (57.0%) were aged 1–3 years, while the fewest were aged 11–18 years. The male-to-female ratio was 1.8:1, and the urban-to-rural ratio was 1.1:1. The most common external causes were foreign bodies (41.7%), exposure to inanimate mechanical forces (25.1%), and falls (22.1%). The most frequently injured body parts were head (72.5%). The total number of unintentional injuries exhibited an increasing trend from 2017–2022, and a decreasing trend from 2022–2023. The urban-rural distribution reversed after 2020. The overall hospitalization cost was 20,810,870.4 USD, with an median cost of 758.7 (556.4, 1,186.2) USD per person. Conclusion Unintentional injuries imposed a heavy burden on society and families. However, the number of cases and the urban-rural distribution showed significant trend changes from 2017–2023. The external causes varied by age group, gender, and region, while prevention and control measures should be developed accordingly.